Miss Understood - Roy, James (North Sydney, N.S.W. : Random House Australia, 2012)
Lizzie doesn't mean to do the wrong thing . . . she's just misunderstood. Lizzie has a history of misunderstandings, but the latest one is bad enough to get her expelled from Our Lady of the Sacred Wimple College. So now she's going to be homeschooled. That's right - from now on her mum will be her teacher. No friends, no playground, nothing but homework. What will Lizzie have to do to prove that she's mature enough to be allowed back to Sacred Wimple? She's prepared to give almost anything a go, but will it end up the same way it usually does - with her being misunderstood all over again? Miss Understood is a warm, funny and moving story by award-winning author James Roy.
Imprint: RHA eBooks Child.
Audience: Juvenile.
Also issued in printed form.
Mode of access: Internet. Refer to the publisher's home page.
System requirements not available.
Vendor-supplied metadata
Keywords: Family & home stories (Children's / Teenage); General fiction (Children's / Teenage); Juvenile Fiction - Family - General (see Also Headings Under Social Situations); Juvenile Fiction - General; Juvenile Fiction - School & Education; Juvenile Nonfiction - Social Situations - Self-esteem & Self-reliance.; Personal & social issues: self-awareness & self-esteem (Children's / Teenage); School stories (Children's / Teenage); Australian; Electronic books